2003
DOI: 10.2320/matertrans.44.1271
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Al Scrap for Fabrication of Al(alloy)/Al<SUB>2</SUB>O<SUB>3</SUB> Composite Material

Abstract: In status quo, Al scrap melt is diluted with pure Al and adjusted its composition for reuse. We studied a method to utilize Al scrap directly for fabricating composite materials, which can be used for machine elements having resistance to abrasion. The composite material is a product of displacement reaction between molten Al scrap and SiO 2 . Its microstructure consists of Al 2 O 3 network and Al alloy among them. In this study, Al alloy was prepared which have a composition of Al scrap due to window frame of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In another work, (Yoshikawa et al, 2003) The microstructural studies showed that the reinforcements were uniformly distributed throughout the specimens examined. In addition, it was reported that the composite materials prepared using scrap exhibited a little higher strength and hardness than Al/Al 2 O 3 composites, and did not break into pieces upon fracture, as occurred in the case of (Al-10 at.% Fe)/Al 2 O 3 samples.…”
Section: Waste Materials As Reinforcing Phase and Matrixmentioning
confidence: 90%
“…In another work, (Yoshikawa et al, 2003) The microstructural studies showed that the reinforcements were uniformly distributed throughout the specimens examined. In addition, it was reported that the composite materials prepared using scrap exhibited a little higher strength and hardness than Al/Al 2 O 3 composites, and did not break into pieces upon fracture, as occurred in the case of (Al-10 at.% Fe)/Al 2 O 3 samples.…”
Section: Waste Materials As Reinforcing Phase and Matrixmentioning
confidence: 90%
“…The details are described in the previous report. 4) The synthesized scrap composition is also listed in Table 1. The glass beads are placed in the bottom of glass tube made of fused silica with one closed end, having 10 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…5) It has been demonstrated that the reaction rate and the mechanical properties are not deteriorated very much if the Al is replaced with the synthesized Al scrap. In the above process, 4) vitreous (pure) silica was utilized as the raw materials, however it is expensive and better to make use of the other silica-based wasted materials. There are many kinds of wasted glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Amphoteric oxide Al 2 O 3 is a common crucible material; its stability is better than that of acidic oxides. Yoshikawa et al (2003) reacted waste-Al with acidic SiO 2 to prepare composite materials. Basic oxides such as MgO and Y 2 O 3 are again more stable than amphoteric oxides.…”
Section: Introductionmentioning
confidence: 99%